Analysis of weight loss rate, color, sugar content, and total acidity in tomatoes during storage with edible coating - Rafli Zulfa Kamil; Fahira Adibah Thalib; Nurwantoro Nurwantoro; Fariz Nurmita Aziz; Heni Rizqiati; Nurul Hasniah (International Journal of Advances in Applied Sciences, 2026)
Tomatoes, as climacteric fruits, offer numerous advantages, making them popular among many individuals. However, they are prone to mechanical and microbiological harm, which is why applying an edible coating is a viable post-harvest handling technique for tomatoes. A combination of corn starch, chitosan, and glycerol serves as an effective edible coating, with corn starch providing hardness, chitosan offering antimicrobial properties, and glycerol acting as a plasticizer. This research seeks to assess the rate of weight loss, color, sugar content, and total acidity in tomatoes during storage with an edible coating. The preparation of the edible coating involves using 2% (w/v) corn starch, 1.5% (w/v) chitosan dissolved in 0.5% (w/v) acetic acid, and 0.25% (w/v) glycerol. The tomatoes were immersed in the edible coating twice, with each immersion lasting 1 minute and a drying period of 5 minutes. Subsequently, the tomatoes were stored for 15 days, with observations made every 5 days. The edible coating has been shown to slow down the deterioration of tomatoes during storage by forming a barrier that restricts the movement of water and air, which are essential for the physicochemical reactions involved in the tomato ripening process.